Empowering seizures awareness: knowledge, attitudes and fears of school staff trained in rescue drugs - Pompili, E; Bert, F; Corradi, A; Gualano, M R; Venuti, S; Siliquini, R (European journal of public health, 2020)
Background The administration of rescue medication at school concerns, in all Europe, students suffering from chronic pathologies for which it may be essential, on doctor's prescription, to take therapy during school hours. About 16% of the school's emergency calls are related to a seizure crisis. In this case, since the parents are absent, the first rescuer is necessarily the school staff, who should be properly trained because prolonged seizures can cause severe harm and even death. Methods Every year, the Local Health Unit “TO3”, in Northern Italy, provides training for school staff to administrate rescue medication at school. A questionnaire survey on knowledge, attitudes and fears towards seizures was conducted during the school year 2019/2020. The same questionnaire was administered to school staff trained for seizures at the end of the course, while the staff trained for other diseases such as diabetes, allergies and asthma completed it before the course. Results 110 questionnaires have been completed. About 60% of the sample had been trained in seizure management at least once in their lifetime. The respondents had a mean age of 48.7±9.6 years and a mean job experience of 17.4±11.2 years. Most of them were females (83%). Median knowledge score (10 points max) in subjects with no seizures training was 6, while it was 8.5 in subjects with seizures training (p < 0.001). The self-reported level of confidence in their own skills to administer rescue medication was high in 10.4% of subjects not trained for seizures and in 63.8% of those trained (p < 0.001). Conclusions Results suggest that medical training for school staff boosts knowledge scores and levels of self-confidence relating to the administration of rescue medication. Moreover, after the training, the school staff changed attitude towards seizures, no longer considered as a problem, and became more aware, less fearful, and more inclined to act in case of need, making school a safer place for all students. Key messages School staff trained in the administration of rescue medication are fundamental to guarantee the right to education for students suffering from chronic pathologies such as seizures. Empowering seizures awareness in schools is very important to change the attitude of school staff no longer considering seizures as a problem, making school a safer place for all European students.